Ingestion and egestion of polystyrene microplastic fragments by the Pacific oyster, Crassostrea gigas. (15th August 2022) - Choi, Hoon; Im, Dong-Hoon; Park, Yun-Ho; Lee, Ju-Wook; Yoon, Sung-Jin; Hwang, Un-Ki
Abstract: Marine microplastics (MPs) pose a risk to human health through accumulation in maricultural organisms, particularly bivalves. Various studies have reported the presence of MP particles in Pacific oysters ( Crasostrea gigas ). In this study, we investigated the size-specific ingestion and egestion of polystyrene (PS) MPs by Pacific oysters. The cultivation density of C. gigas was maintained at 1 L of filtered seawater per oyster (n = 5) during the MP ingestion and egestion experiments. On exposure to 300 n/L of PS MP fragments for 7 d, 60.4% of the PS was ingested within 6 h (7.25 × 10 2  ± 1.36 × 10 2 n/indv.), and the ingestion was saturated at 12 h (1.2 × 10 3  ± 2.2 × 10 2 n/indv.) in C. gigas . The maximum MP ingestion capacity (Igmax ) of a single Pacific oyster was 73.0 ± 16.3 n/g wet weight. Further, 62.9% of the PS MP particles were egested for 7 d from the saturated single C. gigas . Ingestion and egestion varied according to the PS MP size. In the case of <50 μm PS MP, ingestion rate was low but MP amount and net-ingestion efficiency was significantly higher than other PS MP sizes. In addition, egestion, egestion rate, and net-egestion efficiency for <50 μm PS MPs were significantly higher than other PS MP sizes. Therefore, smaller MPs (<50 μm) normally exhibit the highest ingestion and egestion rates; therefore, the 50–300 μm size fraction exhibited the highest residual possibility (particles >1000 μm were excluded). Additionally, considering the net-egestion efficiency, the most economical and efficient depuration period was 24 h. This study clarifies the size-specific MP accumulation in oysters, and the egestion results suggest that the potential risk of MPs to human health through the intake of maricultural products could be reduced by depuration. Graphical abstract: Image 1 Highlights: Polystyrene (PS) microplastic (MP) ingestion began at 6 h and was saturated by 12 h. The ingestion capacity of Crassostrea gigas was 72.9 ± 16.3 n/g PSMP. PSMP fragments sized <50 μm were most readily ingested and egested. C. gigas primarily accumulated PSMP fragments sized 50–300 μm. The most effective depuration period was 24 h, under controlled conditions.